ANALISIS KOMPARATIF BENTUK GELOMBANG OFDM DAN FBMC UNTUK KOMUNIKASI NIRKABEL 5G YANG DITINGKATKAN DAN 6G DI MASA DEPAN - Majd Sultan Ahmed Al-muntaser; Yuliarman Saragih; Din, Insani Abdi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid evolution of wireless communication systems from 1G to 5G has driven the demand for higher data rates, lower latency, improved spectral efficiency, and enhanced resolution. Orthogonal Frequency Division Multiplexing (OFDM) has been adopted as the fundamental waveform for modern wireless systems due to its robustness against multipath fading and ease of implementation. However, certain limitations—including high out-of-band emissions, cyclic prefix overhead, and reduced spectral efficiency—have motivated the exploration of alternative waveform technologies for future sixth-generation (6G) networks. This study presents a comparative analysis of Orthogonal Frequency Division Multiplexing (OFDM) and Filter Bank Multicarrier (FBMC) waveforms for enhanced wireless communication in 5G networks and beyond. A qualitative literature review combined with simulation-based analysis was employed, utilizing findings from previous MATLAB-based investigations conducted in indoor, rural, and urban wireless environments. Performance metrics such as Bit Error Rate (BER), Signal-to-Noise Ratio (SNR), latency, throughput, and spectral efficiency were examined. The results indicate that FBMC offers superior spectral efficiency and lower latency, largely due to the elimination of the cyclic prefix and the implementation of subcarrier filtering. Conversely, OFDM demonstrates lower implementation complexity and maintains robust performance under practical deployment conditions. The study concludes that while OFDM remains the preferred waveform for current 5G deployments, FBMC is a promising candidate for future 6G systems where spectral efficiency and ultra-low latency are critical requirements.